THE GREAT WAVE OFF KANAGAWA AND THE TAIJI DIAGRAM - Wai-Ming Ng (PEOPLE: International Journal of Social Sciences, 2025)
Katsushika Hokusai (1760–1849) created The Great Wave off Kanagawa, a renowned example of Japanese ukiyo-e art, during the Edo period (1603–1868). This iconic masterpiece subtly reflects the philosophy of yin and yang as embodied in the Taiji Diagram. Known for his preference for the S-shaped composition, Hokusai employed this form masterfully—the curling wave and the sky together trace a dynamic S-shape, evoking the Taiji’s symbolic balance. Some Western art historians suggest that The Great Wave was influenced by the Taiji Diagram, a claim supported by compositional and thematic parallels in Hokusai’s other work, The Raging Wave. In that piece, the interplay between male and female wave figures echoes the harmony of opposing forces, similar to the visual and conceptual elements seen in The Great Wave off Kanagawa. Although Hokusai never explicitly mentioned the Taiji Diagram in relation to this ukiyo-e, in my paper I identify five indirect forms of evidence to argue that he may have been inspired by the Diagram when creating this work.